ENVIRONMENT AND EDUCATION: : THE INFLUENCE OF THE ENVIRONMENT ON LEARNING DIFFICULTIES - Rodrigues Santana, Bruna; Santos de Lima, Cristiana; de França Bomtempo, Sarah; Rosa Maia Viola Barreiro, Talitha (Revista Gênero e Interdisciplinaridade, 2022)
The article’s aim is to identify the main factors relating learning difficulties to the interference of the Family, and both social and school environment in one’s life. Considering all aspects as equally fundamental in the individual’s social and cognitive development. As it is understood that learning is a dynamic and interactive process between the child and its surroundings, guaranteeing the appropriation of knowledge and adaptive strategies based on his initiatives and interests and the stimuli he receives from his social environment. The learning process of an individual is influenced by the environment in which he or she is, therefore, this article highlights important factors that favours learning difficulties.